Evolution of a cluster of innate immune genes (β-defensins) along the ancestral lines of chicken and zebra finch - Hellgren, Olof; Ekblom, Robert (Immunome research, 2010)
Avian beta-defensins (AvBDs) represent a group of innate immune genes with broad antimicrobial activity. Within the chicken genome, previous work identified 14 AvBDs in a cluster on chromosome three. The release of a second bird genome, the zebra finch, allows us to study the comparative evolutionary history of these gene clusters between from two species that shared a common ancestor about 100 million years ago. A phylogenetic analysis of the beta-defensin gene clusters in the chicken and the zebra finch identified several cases of gene duplication and gene loss along their ancestral lines. In the zebra finch genome a cluster of 22 AvBD genes were identified, all located within 125 Kbp on chromosome three. Ten of the 22 genes were found to be highly conserved with orthologous genes in the chicken genome. The remaining 12 genes were all located within a cluster of 58 Kbp and are suggested to be a result of recent gene duplication events that occurred after the galliformes- passeriformes split (G-P split). Within the chicken genome, AvBD6 was found to be a duplication of AvBD7, whereas the gene AvDB14 seems to have been lost along the ancestral line of the zebra finch. The duplicated beta-defensin genes have had a significantly higher accumulation of non-synonymous over synonymous substitutions compared to the genes that have not undergone duplication since the G-P split. The expression patterns of avian beta-defensin genes seem to be well conserved between chicken and zebra finch. The genomic comparisons of the beta-defensins gene clusters of the chicken and zebra finch illuminate the evolutionary history of this gene complex. Along their ancestral lines, several gene duplication events have occurred in the passerine line after the galliformes-passeriformes split giving rise to 12 novel genes compared to a single duplication event in the galliformes line. After the duplication events, the duplicated genes have been subject to a relaxed selection pressure compared to the non-duplicated genes, thus supporting models of evolution by gene duplication.